Discovery of novel serine palmitoyltransferase inhibitors as cancer therapeutic agents. Issue 9 (15th May 2018) - Kojima, Takuto; Asano, Yasutomi; Kurasawa, Osamu; Hirata, Yasuhiro; Iwamura, Naoki; Wong, Tzu-Tshin; Saito, Bunnai; Tanaka, Yuta; Arai, Ryosuke; Yonemori, Kazuko; Miyamoto, Yasufumi; Sagiya, Yoji; et al.
Graphical abstract: Abstract: We pursued serine palmitoyltransferase (SPT) inhibitors as novel cancer therapeutic agents based on a correlation between SPT inhibition and growth suppression of cancer cells. High-throughput screening and medicinal chemistry efforts led to the identification of structurally diverse SPT inhibitors4 and5 . Both compounds potently inhibited SPT enzyme and decreased intracellular ceramide content. In addition, they suppressed cell growth of human lung adenocarcinoma HCC4006 and acute promyelocytic leukemia PL-21, and displayed good pharmacokinetic profiles. Reduction of 3-ketodihydrosphingosine, the direct downstream product of SPT, was confirmed under in vivo settings after oral administration of compounds4 and5 . Their anti-tumor efficacy was observed in a PL-21 xenograft mouse model. These results suggested that SPT inhibitors might have potential to be effective cancer therapeutics.